Managing foreign policy decision making with respect to the "two chinas" - Chaplog, Shirley, Marlene (My University, 1997)
The deciding of foreign policy for any Government is complex. This report develops a framework to analyse this complexity with a case study of the key policy change by the South African government to date. The decision to switch diplomatic relations from the Republic of China to the People's Republic of China involved the full range of ideological, political and economic dimensions. Data was gathered from interviews and documents, which was analysed by developing themes and using a coding and matrix system. The study explores the traditional models of decision making, the "Rational Actor", "Organisational Process" and "Bureaucratic Politics", and argues that none alone can explain and predict foreign policy. It considers whether a hybrid model, combining all three, is a satisfactory framework in this case. It concludes that the decisive intervention of President Mandela cannot be incorporated into the traditional models and so a framework called model Z for convenience was developed. Whether President Mandela's (or his successor's) personality and leadership style will determine foreign policy into the millennium and therefore need to be
A research report submitted to the Faculty of Management, University of the Witwatersrand, in partial fulfillment of the requirements fur the degree of Master of Management (in the field of Public and Development Management). Johannesburg, December 1997.